Upaya Transformasi Mindset: Promosi Konvensional Menuju Promosi Media Sosial Pada Komunitas Nen Dit Sakmas - Walter Tabelessy; Merry Margareth Pelupessy; Erlinda Tehuayo; Jacsy Tubalawony (CV. Multi Kreasi Media, 2023)
The problem faced by the Nen Dit Sakmas Community Wain Village is that they still have the mindset to use conventional promotions in today's digital era. Related to that, the purpose of this community service activity is to seek mindset transformation so that this community can switch to using social media promotions. The effort is carried out by applying the method of public education by means of outreach, knowledge and understanding of the importance of promotion through social media with its advantages is conveyed to this community. Therefore, through this activity it is hoped that there will be a transformation from a fixed mindset to a growth mindset so that this community can use social media and can compete with other MSMEs.